FIGURES OF SPEECH IN THE SLEEPING BEAUTY IN THE WOOD - Adani Nur Sabrina (Jurnal Sosial Humaniora dan Pendidikan, 2023)
The readers of literary works are not limited by age and background. Not only grown-up adults, but children also have their own literature texts. This research discussed the figures of speech in one of the children’s literature, namely a fairy tale. The purposes of this research are to find the figures of speech in the tale, classify them into categories, and analyze their implementation in the story. Since the data and analysis of this research are in the form of words, this research used a qualitative method. The source of the data is a famous fairy tale by Charles Perrault entitled The Sleeping Beauty in the Wood. The results show there are thirty-one figures of speech that cover two metaphors, three similes, four synecdoches, eleven personifications, eight hyperboles, two meiosis or understatements, and one paradox.